Warehouse Receipt as Credit Guarantee to Welfare Farmers Based on Pancasila Justice at Bandar Lampung - Angga Pratama (Fakultas Hukum Universitas Lampung, 2023)
A common problem with agriculture in Indonesia is falling prices during the main harvest season. Farmers cannot store their crops longer because they run out of funds and do not have sufficient warehouses. This condition is exploited by middlemen and loan sharks to make huge profits. Then the government tried to overcome these problems through the aspirations of the Warehouse Receipt System (SRG) and Warehouse Receipts to be used as collateral for loans in banks. In implementing Warehouse Receipts for the welfare of farmers, in this case, it is stated in the values of Pancasila, which in essence, justice must be obtained for the welfare of farmers, especially in agricultural commodities, so that at the time of harvest, farmers can get a stable harvest price by using the Warehouse receipt system. In this case, the author takes a normative approach which is carried out by conducting a study of legal science materials or by using library materials known as library research or it can also be supporting legal scholarship such as principles and regulations, especially Law Number 9 of 2011 concerning Amendments to Law Number 9 of 2006 concerning Warehouse Receipt Systems. The results of the study show that in the implementation of SRG in Bandar Lampung city district, government policies are still experiencing problems in their implementation. Among other things, the lack of socialization among farmers, not on target, high interest in the second year for farmers who use WRS, high operational costs of transporting agricultural products from farmers' places to WRS warehouses, and not all banks. Willing to accept warehouse receipt certificates as collateral for bank loans.